Effect of retraction materials on gingival health: A histopathological study - Phatale Sushma; Marawar P; Byakod Girish; Lagdive Sanjay; Kalburge Jitendra (Wolters Kluwer Medknow Publications, 2010)
Background: Gingival retraction methods are used in dentistry for impressions of subgingival crown margins, such as, mechanical, chemical, chemicomechanical, and surgical. These methods may injure the gingival sulcular epithelium. Hence, the present study is carried out to evaluate the effect of different retraction materials, such as, Expasyl, Magic Foam Cord, and impregnated retraction cord on the gingival sulcular epithelium. Materials and Methods: This study included 30 cases of bilateral premolar extraction patients with Loe and Silness gingival index zero. Retraction materials were kept in the dry, isolated labial gingival sulcus for the required time. The retraction materials were removed by rinsing with water. Retracted gingiva of 2 - 3 mm from the gingival margin along with the tooth was extracted and the decalcified sections were microscopically studied. Data analysis: Data were analyzed by applying the chi-square test. Results: This study showed better results with retraction paste as compared to the retraction cord, and there was a significant association between retraction materials and the relative degree of injury to the sulcular epithelium. Conclusion: There is a significant association between retraction materials and gingival sulcular epithelium. It can be stated that impregnated retraction cord, may be used commonly but it needs proper tissue manipulation and is technique sensitive. Newly advanced material in the form of retraction paste like Expasyl or Magic Foam Cord was found to be better than cord as assessed histologically, it respects periodontium.